2019
DOI: 10.1002/ejlt.201900111
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐3 and Polyunsaturated Fatty Acids‐Enriched Hamburgers Using Sterol‐Based Oleogels

Abstract: Obesity and cardiovascular diseases are among the most worrying health problems worldwide. Dietary habits can be catalysts for the rise of these health issues in western countries. In this work, a meat product (pork patties) commonly elaborated with a high fraction of saturated fat is reformulated with an oleogel based on linseed oil (rich in polyunsaturated fatty acids). The oleogel is used for the partial replacement of the solid fat fraction present in pork patties (H‐25 for 25% and H‐75 for 75% of replacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 28 publications
1
22
1
Order By: Relevance
“…Sterol/sterol-ester [165][166][167][168] EC, wax [ 38,[168][169][170][171][172][173][174] Pork skin emulsion [175] Texture, spreadability Pâté EC, wax [ 176,177] EC+ MAG [178] Margarine+ spreads Emulsion stabilization, hardness, melting properties, spreadability…”
Section: Confectionary Productsmentioning
confidence: 99%
“…Sterol/sterol-ester [165][166][167][168] EC, wax [ 38,[168][169][170][171][172][173][174] Pork skin emulsion [175] Texture, spreadability Pâté EC, wax [ 176,177] EC+ MAG [178] Margarine+ spreads Emulsion stabilization, hardness, melting properties, spreadability…”
Section: Confectionary Productsmentioning
confidence: 99%
“…Other authors studied the effect of partial replacement of animal fat (25% and 75%) by linseed oil oleogels, using γ-oryzanol and β-sitosterol as organogelators in pork burgers [ 50 ]. In this case, the reformulation resulted in a significant and progressive decrease of moisture as well as an increase of fat content as the animal fat was replaced.…”
Section: Incorporation Of Lipid Bio-based Ingredients Into Meat Symentioning
confidence: 99%
“…Similar to the previous studies, the inclusion of oleogels reduced hardness and increased the color parameters (L* and b*). The sensory analysis also showed that the reformulation decreased the sensory acceptability, and a preference test revealed a clear preference for the control samples (more than 80%) [ 50 ].…”
Section: Incorporation Of Lipid Bio-based Ingredients Into Meat Symentioning
confidence: 99%
“…The hamburger formulated with 25% oleogel and subcutaneous pork fat displayed similar textural parameters; it was also secondly preferred in the sensory evaluation, after the reference hamburger. The cost evaluation of producing oleogel based hamburgers were also analyzed, resulting that for a 25% containing oleogel there are no extra costs for purchasing the ingredients [90].…”
Section: Meat Pattiesmentioning
confidence: 99%